The Basque Phase of Spain's First Carlist War. - Coverdale, John F. (Princeton legacy library., 2014)
This work explores the background and first two years of the First Carlist War--a conflict that pitted conservative northern peasants against the liberal Madrid government in the largest and most sustained case of armed peasant resistance to modernization in nineteenth-century Europe. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important b.